Consumers’ Preference on Consumption of Brandy among Other Alcoholic Beverages in Kathmandu Valley, Nepal (Quest Journal of Management and Social Sciences, 2022)
Design/Methodology/Approach: This cross-sectional study obtained data from 269 respondents using purposive sampling. We use self-administrative survey technique to collect the data and applied structured questionnaire. Binary logistic regression is applied for analyzing the factors determining the brandy consumption in Kathmandu valley, Nepal.Purpose: This study analyzes the consumers’ preferences for brandy among other alcoholic beverages.Findings: People in Kathmandu valley were found to have low preference for brandy compared to whisky and wine. The socio-demographic study towards brandy preference showed that the people lack adequate information about brandy like brand name, raw materials used and also the alcohol content in brandy. The statistically significant positive relationship has been observed between knowing of alcohol content and the preference for brandy as well as the level of education and the brandy consumption behavior among people.Research limitations/implications: These research findings may have managerial implications, especially in hospitality industry and implications for brandy product marketing.Originality/Value: Further, the findings can help producers to produce brandy products and develop strategy for substituting whisky and wine, and help individuals make informed decisions about drinking.